Methodological review of a social indicator monitoring system : an inter-ministerial product (Government of Jamaica [Kingston]JM, 2000)
Seeks to determine under what conditions and in what form the Social Indicator Monitoring System (SIMS) will be possible.
Keywords: SOCIAL INDICATORS